Pengaruh Karakteristik Individu, Karakteristik Pekerjaan dan Karakteristik Organisasi terhadap Kinerja Pegawai (Studi pada Politeknik Kotabaru) - Dayat IKhsan Hajati; Dwi Wahyu Artiningsih; Hj. Nurul Wahyuni (Universitas Lambung Mangkurat, 2018)
The aims of this research were 1) to analyze the significant effect of individual characteristics on employees’ performance partially, 2) to analyze the significant effect of job characteristics on employees’ performance partially, 3) to analyze the significant effect of organizational characteristics on employees’ performance partially, 4) to analyze the significant effect of individual characteristics, job characteristics and organizational characteristics on employees’ performance simultaneously.The types of research was causal research. The populations were employees at Polytechnic of Kotabaru with 39 peoples as samples in this research and sampling technique uses saturated sampling technique. The method of data analysis used multiple regression analysis.The results of research showed that 1) individual characteristics have insignificant effect on employees’ performance partially, with the effect was -21,9%, 2) job characteristics have significant effect on employees’ performance partially, with the effect was 38,8%, 3) organizational characteristics have significant effect on employees’ performance partially, with the effect was 43,3%, 4) individual characteristics, job characteristics and organizational characteristics have significant effect on employees’ performance simultaneously, with the simultaneous effect was 35,3%. Keywords: Individual Characteristics, Job Characteristics, Organizational Characteristics, Employees’ Performance